(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2009)
The corresponding author Mushtaq Ahmed was added on 3/12/2009. Introduction: Bangladesh is a developing country of South Asia. Rural population of this country is mostly dependant on agricultural cultivations. With the advance of times, pesticides are, now a days routinely used for modern cultivation method. These are readily available as over the counter (OTC) drugs in village shops and act as a common agent for suicidal purpose after trivial family problems. Currently pesticide self poisoning has become a major clinical problem of the developing countries killing around 3,00,000 people each year. Industrialized countries are also affected by it, where a significant proportion of suicidal death are caused by Pesticide ingestion. Of course, such poisoning is seldom included as a priority for heath research in this country. doi: 10.3329/jafmc.v5i1.2851 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.41-45